Tax amnesty and taxpayer morality in predicting taxpayer compliance - Devano, Sony; Mulyani, Sri; Winarningsih, Srihadi; Ghani, Erlane (International Journal of Applied Economics, Finance and Accounting, 2024)
This study examines how the implementation of tax amnesty affects the morality of taxpayers and how well they follow the rules, as well as how the morality of taxpayers affects those two things. This study is a quantitative study using a survey instrument distributed to tax officers at the West Java Regional Tax Service Office. Questionnaires were sent randomly to 1,354 account representatives in 38 tax service offices. Hypothesis testing was carried out using the structural equation modelling approach. The findings revealed that the implementation of a tax amnesty could improve taxpayer morale and compliance. Taxpayer morality can mediate a good relationship between the implementation of tax amnesty and taxpayer compliance. Other findings showed that the implementation of tax amnesties had a greater effect on taxpayer compliance than taxpayer morality. It is implied that taxpayers will see an increase in tax audit activities after the implementation of the tax amnesty to encourage taxpayer compliance in the future and calculate the amount of tax liability correctly. In addition, paying taxes has a positive influence on taxpayers, which becomes a moral aspect of increasing taxpayer compliance. The findings of this study can assist the tax authorities in coming up with a model to measure taxpayer compliance from the tax officer's perspective.